Intra-articular ossicle in interphalangeal joint of the great toe and clinical implication - Suwannahoy P. (2017)
Failure of closed reduction for an interphalangeal joint dislocation of the great toe resulted from an intraarticular ossicle interposed between the articular cartilages of the phalanges. The knowledge concerning the intra-articular ossicle is unclear. A study was thus carried out on 100 fresh great toes to document the appearance, number, size, and location of the intra-articular ossicle found in the interphalangeal joint of the great toe. Roentgenographic studies of the joint revealed 86% of bony mass representing either the sesamoid bone or the intra-articular ossicle. Anatomical studies revealed no sesamoid bone in the Xexor hallucis longus tendon. There was 88% of intra-articular ossicle on the dorsal surface of the plantar capsule of the interphalangeal joint. A medial surgical approach to reduce the irreducible dislocation is thus suggested as easier and safer than other approaches. © 2011 Springer-Verlag.